Answer:
x = -2
Step-by-step explanation:
so how i would do it is
-4x + (-3) = -x +3 you would subtract 3 from the right side and add/ subtract it onto the left
then you have
-4x + (-6) = -x next you take the -4x and you would add it to the right side to get
-6 = 3x
lastly you divide -6 / 3 to get
x = -2
would love if i could have brainlist
Answer:
48: 24
Step-by-step explanation:
divide.
It’s either d or A but I’m sure it’s A
Answer:
Pair 1.
Step-by-step explanation:
On pair 1, shape A can go into shape B with a rotation.
Pair 2 would be a translation.
Pair 3 would be a reflection across the x-axis.
Pair 4 would be a reflection across the y-axis.